HISTOLOGI LIVER BURUNG PUYUH DENGAN PEMBERIAN MINYAK ATSIRI BAWANG PUTIH (Liver Histologic of Quail with Administeration of Garlic Volatile Oil) - Andi Mushawwir; An An Yulianti; Nono Suwarno (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
Sixty-four of female quails, twenty-two weeks old, were used in the current study to evaluate the potential of volatile oil from garlic extract in improving the histological liver of the quails. Volatile oil isolated from garlic by using destilated technique. This study was designed according to completely randomized design, consisted of four treatment groups and six replications. Each treatment group consisted of 16 quails, with supplemental volatile oil (VO) by orally, as follow L0=without of VO; L1= VO of 75 mL; L2= VO of 100 mL and L3= VO of 125 mL. Liver tissue samples were collected using a fixative solution and the liver samples were used to determine the liver histological parameters (necrosis, apoptosis, fat degeneration, hydropic degeneration, acute inflammation, hemorrhagic) by a Mallory-asan technique dan binocular microscope. The current study showed that overall results indicated a significant treatment effect (P<0,05) for the liver histological condition. In conclusion, VO resulted in supplemented levels that significantly raised protein and lipid anabolic and induced hormone signal related growth liver tissue